Revealing the influence of microbiota on the quality of Pu-erh tea during fermentation process by shotgun metagenomic and metabolomic analysis. (December 2018) - Li, Zhongyuan; Feng, Cuixia; Luo, Xuegang; Yao, Huiling; Zhang, Dechun; Zhang, Tongcun
Abstract: Multispecies microbial community in natural solid-state fermentation (SSF) is crucial for the formation of Chinese Pu-erh tea's unique quality. However, the association between microbiota and tea quality are still poorly understood. Herein, shotgun metagenomic and metabolomic analysis showed that significant variations in composition of microbiota, collective functional genes, and flavour compounds occurred during SSF process. Furthermore, the formation pathways of the dominant flavours including theabrownin, methoxy-phenolic compound, alcohol and carvone were proposed. Moreover, biological interaction networks analysis among functional core microbiota, functional genes, and dominant flavours indicated Aspergillus was the main flavour-producing microorganism in the early SSF, while many other genera including Bacillus, Rasamsonia, Lichtheimia, Debaryomyces were determined as the functional core microorganism for flavours production in the late SSF. This study provides a perspective for bridging the gap between the microbiota and quality in Pu-erh tea, and benefited for further optimizing production efficiency and product quality. Graphical abstract: Image 1 Highlights: The fermentated mechanism of Pu-erh tea was firstly studied by metagenomic and metabolomic approaches simultaneously. The biosynthesis or metabolic pathways of the dominant flavour compounds in Pu-erh tea were proposed. Aspergillus, Bacillus, Rasamsonia, Lichtheimia and Debaryomyces were the functional core microorganism for flavours production.